THE JEOPARDIZED SITUATION OF ELECTRONIC WASTE IN BANGLADESH: CAN CUSTOMIZED POLICY APPROACH SOLVE THE CHALLENGE? - Khalid Md. Bahauddin (Geography, Environment, Sustainability, 2016)
Electronic waste (e-waste) is one of the fastest-growing pollution problems worldwide given the presence if a variety of toxic substances which can contaminate the environment and threaten human health, if disposal protocols are not meticulously managed. In Bangladesh almost 2.7 million metric tons of e-waste generated per year. Of this amountonly 20 to 30 percent is recycled and the rest of the waste is released in to landfills,  rivers, drains lakes, canals, open spaces which are very hazardous for the health and environment. Since Bangladesh is in the stream of rapid technological advancement, it is seldom to take necessary steps to avoid the future jeopardized situation because of e-waste. The current practices of e-waste management in Bangladesh suffer from a number of drawbacks like the difficulty in inventorisation, unhealthy conditions of informal recycling, inadequate legislation and policy, poor awareness and reluctance on part of the corporate to address the critical issues. The paper highlights the associated issues and strategies to address this emerging problem, analyses the policy and its gaps. Therefore, this paper also suggest that e-waste policy development may require a more customized approach where, instead of addressing e-waste in isolation, it should be addressed as part of the national development agenda that integrates green economy assessment and strategic environmental assessment as part of national policy planning. Finally this work also suggests some alternative strategies and approaches to overcome the challenges of e-waste.